Pengaruh Senam Lansia terhadap Penurunan Tekanan Darah pada Lansia - Eviyanti Eviyanti; Heny Noor Wijayanti; Sitti Khadijah (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2021)
Most diseases in the elderly are non-communicable diseases such hypertension, arthritis,stroke,Chronic Obstructive Pulmonary Disease(COPD) and DM. Hypertension is the highest prevalence of disease undergone by the elderly. Efforts to reduce blood pressure in hypertension sufferers can be made non-pharmacologically. One of the non-pharmacological efforts is physical exercise (sports). The result of a preliminary study in 128 elderly people indicated that 67 had hypertension, and the elderly routinely did elderly gym five times a week. Objective: To reveal the effects of elderly gym on reducing blood pressure in the elderly at BPSTW Yogyakarta of Abiyoso unit.This research employed preexperimental quantitative research using One Group Pretest-Post Design. The research subjects were elderly with hypertension who lived at BPSTW of Sleman Regency,Yogyakarta. Samples were taken using purposive sampling. Data were analyzed using dependent t-test and Wilcoxon.The results of systolic blood pressure analysis before and after the elderly gym using paired t-test indicated p-value of 0.000 which was less than 0.05(p<0.05) and diastolic blood pressure using Wilcoxon test indicated p-value of 0.039 which was less than 0.05(p<0.05), so that Ho was rejected. There is an effect of elderly gym on reducing systolic and diastolic blood pressure in elderly with hypertension at BPSTW Yogyakarta of Abiyoso unit.